Morpho physio characteristics of climate resilient wheat varieties sown under different sowing dates under rainfed conditions of Pakistan - Jhanzab, Hafiz Muhammad; Tanveer, Sikander Khan; Abbas, Syed Haider; Hussain, Imtiaz; Qamar, Maqsood; Waqar, Sundas (Journal of Pure and Applied Agriculture, 2023)
Erratic climate has influenced the optimum time of sowing of wheat and grain production by variations in temperature during growth period of crop. Production of wheat is highly sensitive to elevated temperatures. Suitable time of sowing is very imperative to achieve higher yield on sustainable basis. An investigation was carried out to check the response of growth and yield of different advanced lines under three varying planting windows. For this purpose, a field investigation was taken at National Agricultural Research Center (NARC) area Islamabad which was laid down in randomized design with three repeats. Results revealed that maximum plant population / m2, plant height (cm), and leaf area (cm2) were recorded with SD1 (03 Nov), followed by SD2 (26 Nov) and minimum response was recorded with SD3 (03 Dec). Similarly, yield & yield attributes were significantly influenced by sowing of wheat under different sowing dates. Maximum no. of tillers/m2, spike length (cm), and biological yield were recorded with SD1, followed by SD2 and minimum was recorded with SD3. Significantly and maximum 1000-grains weight and yield kg/ha was recorded with SD1. Among, genotypes significantly maximum yield was obtained with NR-499. In conclusion, wheat planted on SD1 produced maximum yield as compared with other planting windows.